Study of arsenic accumulation in rice and evaluation of protective effects of Chorchorus olitorius leaves against arsenic contaminated rice induced toxicities in Wistar albino rats. Issue 1 (December 2016) - Hosen, Saeed; Das, Dipesh; Kobi, Rupkanowar; Chowdhury, Dil; Alam, Md; Rudra, Bashudev; Bakar, Muhammad; Islam, Saiful; Rahman, Zillur; Al-Forkan, Mohammad
Abstract Background In the present study, we investigated the arsenic accumulation in different parts of rice irrigated with arsenic contaminated water. Besides, we also evaluated the protective effects ofCorchorus olitorius leaves against arsenic contaminated rice induced toxicities in animal model. Methods A pot experiment was conducted with arsenic amended irrigation water (0.0, 25.0, 50.0 and 75.0 mg/L As) to investigate the arsenic accumulation in different parts of rice. In order to evaluate the protective effects ofCorchorus olitorius leaves, twenty Wistar albino rats were divided into four different groups. The control group (Group-I) was supplied with normal laboratory pellets while groups II, III, and IV received normal laboratory pellets supplemented with arsenic contaminated rice, C. olitorius leaf powder (4 %), arsenic contaminated rice plusC. olitorius leaf powder (4 %) respectively. Different haematological parameters and serum indices were analyzed to evaluate the protective effects ofCorchorus olitorius leaves against arsenic intoxication. To gather more supportive evidences ofCorchorus olitorius potentiality against arsenic intoxication, histopathological analysis of liver, kidney, spleen and heart tissues was also performed. Results From the pot experiment, we have found a significant (p  ≤ 0.05) increase of arsenic accumulation in different parts of rice with the increase of arsenic concentrations in irrigation water and the trend of accumulation was found as root > straw > husk > grain. Another part of the experiment revealed that supplementation ofC. olitorius leaves with arsenic contaminated rice significantly (p  < 0.05) restored the altered haematological parameters and other serum indices towards the normal values. Arsenic deposition pattern on different organs and histological studies on the ultrastructural changes of liver, kidneys, spleen and heart also supported the protective roles ofCorchorus olitorius leaves against arsenic contaminated rice induced toxicities. Conclusion Arsenic accumulation in different parts of rice increased dose-dependently. Hence, for irrigation purpose arsenic contaminated water cannot be used. Furthermore, arsenic contaminated rice induced several toxicities in animal model, most of which could be minimized with the food supplementation ofCorchorus olitorius leaves. Therefore, Corchorus olitorius can be used as a potential food supplement to the affected people of arsenic prone zone to ensure the food security.